Susie King Taylor : nurse, teacher & freedom fighter - Dunbar, Erica Armstrong; Buford, Candace (Rise, risk, remember: incredible stories of courageous Black women., 2023)
A groundbreaking figure in every sense of the word, Susie King Taylor (1848-1912) was one of the first Black nurses during the Civil War, tending to the wounded soldiers of the 1st South Carolina Volunteer Infantry Regiment. Afterward, she was a key figure in establishing a postbellum educational system for formerly bonded Black people, opening several dedicated schools in Georgia. Taylor was also one of the first Black women to publish her memoirs. Even as her country was at war with itself, Taylor valiantly fought for the rights of her people and demonstrated true heroism.